If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 6 = 8x + 42 Reorder the terms: 6 + 12x = 8x + 42 Reorder the terms: 6 + 12x = 42 + 8x Solving 6 + 12x = 42 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 6 + 12x + -8x = 42 + 8x + -8x Combine like terms: 12x + -8x = 4x 6 + 4x = 42 + 8x + -8x Combine like terms: 8x + -8x = 0 6 + 4x = 42 + 0 6 + 4x = 42 Add '-6' to each side of the equation. 6 + -6 + 4x = 42 + -6 Combine like terms: 6 + -6 = 0 0 + 4x = 42 + -6 4x = 42 + -6 Combine like terms: 42 + -6 = 36 4x = 36 Divide each side by '4'. x = 9 Simplifying x = 9
| 1/6x-2/7=4/7 | | f(x)=x^2+7x-7 | | (2x+1)(9x+b)=6x^2-5x+c | | 7.93-15.29v=0.66v | | 77=.5(7)(9+b) | | 6000=40w+w^2 | | 2(2c-3)-7=2c+5 | | a/4=32 | | 9x+1.5=19.5 | | -5w+4w^2+9=0 | | 6a-4ifa=7 | | 30-15x+6x=32+16 | | 4x+31=-x+1 | | 4-11=3 | | (4x^2-32x-26)/(x-9) | | 2=-3d+14 | | 3+8x=-3(-1-7x) | | -15=c/9-10 | | k=25+10x | | (7-z)(3z-8)=0 | | 48x^2-x-15=0 | | 2(x+4)+6=50 | | -5(-3p+3)=8(6p-6) | | (3x-7)(4x+4)=0 | | 0.3=x(1+x) | | 88=2(6p+8) | | -2(y-6)+1=0 | | X(y+5)=66 | | -65=-8x-9 | | 2a^2+8ab=0 | | 2/9*9-4 | | lnx(x^4/4) |